The Sulu zone: a maritime cultural complex - Quintero, Desiree A. (Sunway University Press, 2024)
A Maritime Cultural Complex revisits enduring links for the conceptualisation of the Sulu Zone as a present-day cultural complex. Honouring Ric Trimillos, a leading ethnomusicologist researching and supporting the study of music and dance in the southern Philippines since 1960, this volume explores heritage, language, social, and political facets in the Southern Philippines, the east Malaysian state of Sabah, east Kalimantan, Central and North Sulawesi in Indonesia, and the surrounding Sulu and Celebes seas. This project ultimately seeks to contribute to society’s understanding of the history, contemporary cultures, and rich traditions of communities within the Sulu Zone.